Tim3 binding to galectin-9 stimulates antimicrobial immunity - Jayaraman, Pushpa (The Rockefeller University Press, 2010)
T cell immunoglobulin and mucin domain 3 (Tim3) is a negative regulatory molecule that inhibits effector T(H)1-type responses. Such inhibitory signals prevent unintended tissue inflammation, but can be detrimental if they lead to premature T cell exhaustion. Although the role of Tim3 in autoimmunity has been extensively studied, whether Tim3 regulates antimicrobial immunity has not been explored. Here, we show that Tim3 expressed on T(H)1 cells interacts with its ligand, galectin-9 (Gal9), which is expressed by Mycobacterium tuberculosis–infected macrophages to restrict intracellular bacterial growth. Tim3–Gal9 interaction leads to macrophage activation and stimulates bactericidal activity by inducing caspase-1–dependent IL-1β secretion. We propose that the T(H)1 cell surface molecule Tim3 has evolved to inhibit growth of intracellular pathogens via its ligand Gal9, which in turn inhibits expansion of effector T(H)1 cells to prevent further tissue inflammation.